COMPARISON OF DIFFERENT STRATEGIES OF ANTIHYPERTENSIVE THERAPY IN OUT-PATIENT CLINIC - O. A. Plejko; A. O. Konradi (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To compare different strategies of start antihypertensive therapy in out-patients.Material and methods. 120 out-patients with arterial hypertension (HT) 1-2 stages were included in the study and randomized in 3 groups. Patients of group «A» received start treatment in compliance with age, clinical features and mechanisms of hypertension. Patients of group «B» received step-by-step start antihypertensive therapy based on doses titration and addition of the second (third) drug if necessary. Patients of group «C» received fixed drug combination with addition of other antihypertensive medicines if necessary. Decrease of BP level and number of visits were used as criteria of therapy efficacy. Pharmacoeconomic analysis of antihypertensive therapy was done in all groups.Results. Strategy of HT start therapy in group «C» had advantages in speed of blood pressure normalization, number of necessary visits and in pharmacoeconomic efficacy in comparison with the strategies in group «A» and «B».Conclusion. HT start therapy with implementation of fixed low dose combination leads to the best result in comparison with other strategy based on step-by-step drug replacement (as well as their combining) or monotherapy dose titration.